Distress in the care of people with chronic low back pain: insights from an ethnographic study - Dillon, Miriam; Olson, Rebecca E.; Plage, Stefanie; Miciak, Maxi; Window, Peter; Stewart, Matthew; Christoffersen, Anja; Kilner, Simon; Barthel, Natalie; Setchell, Jenny (Frontiers in Sociology, 2023)
Introduction Distress is part of the experiences and care for people with chronic low back pain. However, distress is often pathologised and individualised; it is seen as a problem within the individual in pain and something to be downplayed, avoided, or fixed. To that end, we situate distress as a normal everyday relational experience circulating, affecting, moving in, through, and across bodies. Challenging practices that may amplify distress, we draw on the theorisation of affect as a relational assemblage to analyse physiotherapy clinical encounters in the care of people with chronic low back pain. Methods Adopting a critical reflexive ethnographic approach, we analyse data from a qualitative project involving 15 ethnographic observations of patient-physiotherapist interactions and 6 collaborative dialogues between researchers and physiotherapists. We foreground conceptualisations of distress— and what they make (im)possible—to trace embodied assemblage formations and relationality when caring for people with chronic low back pain. Results Our findings indicate that conceptualisation matters to the clinical entanglement, particularly how distress is recognised and navigated. Our study highlights how distress is both a lived experience and an affective relation—that both the physiotherapist and people with chronic low back pain experience distress and can be affected by and affect each other within clinical encounters. Discussion Situated at the intersection of health sociology, sociology of emotions, and physiotherapy, our study offers a worked example of applying an affective assemblage theoretical framework to understanding emotionally imbued clinical interactions. Viewing physiotherapy care through an affective assemblage lens allows for recognising that life, pain, and distress are emerging, always in flux. Such an approach recognises that clinicians and patients experience distress; they are affected by and affect each other. It demands a more humanistic approach to care and helps move towards reconnecting the inseparable in clinical practice—emotion and reason, body and mind, carer and cared for.